2017
DOI: 10.1016/j.jviromet.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

A Luciferase Immunoprecipitation System (LIPS) assay for profiling human norovirus antibodies

Abstract: A luciferase immunoprecipitation systems (LIPS) assay was developed to define the antigenic specificity and titer of antibodies directed against human norovirus (HuNoV). Recombinant proteins, expressed by plasmid constructs encoding Renilla luciferase (Ruc) fused to the full-length HuNoV major capsid protein (VP1) (Ruc-antigen), were generated for ten HuNoV strains. In addition, subdomain constructs Ruc-Shell (S) and Ruc-Protruding (P) were engineered for a representative GII.4 norovirus (strain GII.4/2006b). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…The assay showed the same sensitivity as the one observed when human sera were tested in parallel by the commercial ELISA (Supplemental Table 3). In addition, LIPS sensitivity has been extensively described in different studies and demonstrated to be at least as sensitive as plaque reduction neutralization test and ELISA (Burbelo et al, 2012; Tin et al, 2017; Crim et al, 2019). We therefore conclude that the different viruses we studied are not (or very rarely) transmitted to humans and cattle (<0.017% and <0.047%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The assay showed the same sensitivity as the one observed when human sera were tested in parallel by the commercial ELISA (Supplemental Table 3). In addition, LIPS sensitivity has been extensively described in different studies and demonstrated to be at least as sensitive as plaque reduction neutralization test and ELISA (Burbelo et al, 2012; Tin et al, 2017; Crim et al, 2019). We therefore conclude that the different viruses we studied are not (or very rarely) transmitted to humans and cattle (<0.017% and <0.047%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…As a sensory component of hybrids, various biospecific polypeptides were applied—antibodies or their fragments [ 111 , 112 , 113 , 114 ], antigens [ 115 , 116 , 117 , 118 ], polypeptides with special binding ability [ 119 , 120 , 121 , 122 ], GFP and its color variants [ 123 , 124 , 125 , 126 , 127 , 128 , 129 ], etc. Based on the phenomenon of assembling split luciferase derivatives, a whole spectrum of homogeneous methods has been developed [ 125 , 126 , 127 , 128 , 129 ] and applied for studying protein–protein/ligand interaction [ 130 , 131 , 132 , 133 ], protein activity [ 134 , 135 ], and protein folding [ 136 , 137 ].…”
Section: Ctz-dependent Luciferase Analytical Applicationmentioning
confidence: 99%
“…antibodies) against potentially pathogenic bacteria in the HGM transplants, all piglets received 60 ml gamma-irradiated, non-heat treated porcine serum (Rocky Mountain Biologicals) via three intraperitoneal injections at 24, 30 and 36 h post derivation. The porcine serum was screened using a luciferase immunoprecipitation system assay [53], and no antibodies against a broad range of genotype of HuNoVs, including GI. [45].…”
Section: Gnotobiotic Pigs and Treatmentsmentioning
confidence: 99%